Sliding contention window (SCW) towards backoff range-based service differentiation over IEEE 802.11 wireless LAN networks. - Nafaa, A.
A number of works have tried to adjust the contention window in order to provide differentiated quality of service in IEEE 802.11-based wireless networks. By giving different service classes different CWs, the distribution of backoff intervals (chosen randomly, on the interval [O, CW]) will reflect the desired service classes. However, these protocols cannot deliver firm service guarantees while maintaining high network utilization, particularly under congested network conditions. In this article we propose a new MAC protocol featuring a sliding CW (SCW) for each network flow. The SCW dynamically adjusts to changing network conditions, but remains within a per-class predefined range in order to maintain a separation between different service classes. Each flow's SCW reacts based on the degree to which class-defined QoS metrics are satisfied. Simulation results show that compared to the enhanced distributed coordination function (EDCF) scheme of 802.11e, SCW consistently excels, in terms of network utilization, strict service separation, and service-level fairness.
Keywords: IEEE 802.11 wireless LAN networks; MAC protocol; Backoff intervals distribution; Backoff range-based service differentiation; Class-defined QoS metrics; Congested network conditions; Different service classes; Differentiated quality of service; Enhanced distributed coordination function scheme; Network utilization; Sliding contention window